2010
DOI: 10.1111/j.1464-5491.2010.02956.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns in overweight and obesity in Type 1 diabetes

Abstract: Background Time trends in overweight and obesity in the general population have been well documented; however, temporal patterns in type 1 diabetes (T1D) have not been thoroughly investigated. We therefore assessed temporal patterns in overweight and obesity and predictors of weight change in 589 individuals from the Pittsburgh Epidemiology of Diabetes Complications (EDC) Study, a cohort of childhood onset T1D. Methods Participants were first seen in 1986–1988, when mean age and diabetes duration were 29 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
156
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(187 citation statements)
references
References 21 publications
(28 reference statements)
19
156
1
1
Order By: Relevance
“…The current study also identified any insulin exposure adjusted for other covariates and baseline BMI to be significant predictors of weight gain in the cohort of patients observed. These findings are consistent with those of Conway et al [1] in a longitudinal study to determine the prevalence and incidence of overweight and obesity in a cohort of 589 type 1 DM patients followed up over at least 18 years.…”
Section: Researchsupporting
confidence: 82%
See 3 more Smart Citations
“…The current study also identified any insulin exposure adjusted for other covariates and baseline BMI to be significant predictors of weight gain in the cohort of patients observed. These findings are consistent with those of Conway et al [1] in a longitudinal study to determine the prevalence and incidence of overweight and obesity in a cohort of 589 type 1 DM patients followed up over at least 18 years.…”
Section: Researchsupporting
confidence: 82%
“…The finding that a higher baseline HbA1c predicted a larger and statistically significant increase in subsequent BMI in patients exposed to the twice-daily biphasic insulin dosage regimen when compared with the basal NPH plus prandial regular insulin regimen group in this study population was consistent with observations by Nansel et al, [10] Williams et al [11] and Conway et al [1] These researchers found that IIT and a higher baseline HbA1c were predictors of weight gain in patients in their respective settings. The current study also identified any insulin exposure adjusted for other covariates and baseline BMI to be significant predictors of weight gain in the cohort of patients observed.…”
Section: Researchsupporting
confidence: 81%
See 2 more Smart Citations
“…Considering the annual cost of type 1 diabetes care to the individual, estimated to be $6,288 per year in a 2010 paper [2] and the increasing price of insulin [3], effective and realistic low/no cost strategies to improve glycemic control are needed not only to reduce the expense to the individual with type 1 diabetes, but also to prevent the short and long term complications of poor glycemic control and minimize the negative consequences of high insulin dosages, such as possible weight gain [4].…”
Section: Introductionmentioning
confidence: 99%